Syndrome-Based Prescription to Optimize Psychotropics: Are CHROME Criteria a Game Changer? - Muñiz, Ruben; López-Alvarez, Jorge; Agüera-Ortiz, Luis; Perea, Luis; Olazarán, Javier (Frontiers in Psychiatry, 2021)
A variety of medical and social factors have contributed over the last decades to the overuse of psychotropic drugs in people with dementia. One social factor is probably the frequent failure to provide adequate person-centered care, be it in the community or in institutional settings. This unfortunate reality has been reacted upon with numerous guidelines to reduce prescriptions of the most dangerous drugs (e.g., neuroleptics). Each psychotropic drug prescription can in principle be assessed around three dimensions: a) adequate, b) inadequate, and c) chemical restraint. The CHemical Restraints avOidance MEthodology (CHROME) defined chemical restraint as any prescription based on organizational convenience, rather than justified with medical diagnosis. Two validation studies revealed that one of the main medical reasons of over- and miss-prescriptions was symptom-based prescription. By switching to syndrome-based prescription, a large proportion of drugs could be de-prescribed and some re-adjusted or kept. Paucity of research and weakness of data are not conclusive about the adequacy of specific drugs for the myriad of cases presented by patients with dementia and comorbid conditions. Clinical practice, however, leads us to believe that even under optimal care conditions, psychotropics might still contribute to quality of life if based on an adequate diagnosis. This article explains the rationale that underlies a syndromic approach aimed at optimizing psychotropic treatment in people with dementia whose significant suffering derives from their thought, affective, or behavioral problems. The results of previous validation studies of this new methodology will be discussed and conclusions for future results will be drawn.